Investigating the effect of expected travel distance on individual descent speed in the stairwell with super long distance. (September 2021) - Xu, Xingpeng; Fang, Zhiming; Ye, Rui; Huang, Zhongyi; Lu, Yao
Highlights: Subject repeat the movement from 12th floor to the ground up to 11 times. A new point is proposed and verified, that is, as the expected movement distance increases, the movement speed of the person will decrease. The relation between the increase rate of evacuation distance and the decrease rate of speed is presented. With the increase of expected evacuation distance, the speed decrease rate of the male is greater than that for female. Fatigue also has an important effect on the descent speed. Abstract: Currently, there are an increasing number of super high-rise buildings in urban cities, and the issue of evacuation in emergencies from super-long evacuation distance in stairwells comes to the fore. An evacuation experiment was carried out in Shanghai Tower (Fang et al., 2020), it was found that the evacuation speed of pedestrians evacuated from the 126th floor was always slower than that of those from the 117th floor. Therefore, we propose a hypothesis that the expected evacuation distance will affect pedestrians' movement speed. Pedestrians will adjust the evacuation speed according to the expected evacuation distance, which may be caused by psychological expectation. In order to verify our conjecture, we conduct an experiment in a 12-storey office building, that is, to study whether there would be an influence and what kind of influence would be caused on speed by setting the evacuation distance for participants in advance. According to the results, we find that with the increase of expected evacuation distance, the movement speed of pedestrians will decrease, which confirms our hypothesis. The groups who completed 8 laps had the least evacuation distance, and its average speed is far faster than that of G_11 with longest evacuation distance. Affecting by psychological factors, the individual average descending speed of G_5 + 3 is all over 1.07 m/s in each lap of 8 laps and the maximum average speed is 1.30 m/s while G_11 has the lowest average individual descent speed (the maximum average speed is only 1.09 m/s) in 7 scenarios. Fatigue has an important effect on the descent speed, and the descent speed tends to decrease with the increase of evacuation distance. After the rest, the speed of male, female and all participants increased by 28.0%, 28.5% and 27.7%, respectively. At the same time, we give the relation between the increase rate of evacuation distance and the decrease rate of speed. It also can be found that with the increase of expected evacuation distance, the speed decrease rate of the male (the slope of the downward trend is −0.183) is greater than that for females (the slope of the downward trend is −0.138). In addition, we study the effects of actual evacuation distance, sex, BMI on evacuation speed. Finally, we obtain the correlation between heart rate and speed. The results in this paper are beneficial to the study of pedestrians' characteristics in the long and super-long distance evacuation.